Exploratory single crosses of purple maize for pericarp and cob pigment production - Ramírez Díaz, José Luis; Ledesma Miramontes, Alejandro; Salinas Moreno, Yolanda; Alemán de la Torre, Ivone; Dhliwayo, Thanda; Vidal Martínez, Víctor Antonio (Agronomía Mesoamericana, 2025)
Introduction. Plant pigments represent an alternative to artificial colorants and contribute to the consumption of healthier foods. Objective. To evaluate, both in field and laboratory, exploratory single crosses (ESCs) of maize purple grain and cob developed using random lines, to assess the integration of the heterotic pattern B-49N x B-41N. Material and methods. The research was conducted in Tepatitlán, Jalisco, Mexico, during 2021 and 2022. ESCs were formed using six S5 lines from the B-49N population and four S3 lines from B-41N, all with purple grain and cob. In 2022, the crosses and five controls were evaluated under rainfed conditions in the same location, using a randomized complete block experimental design with three replications. Each plot consisted of a single row, 4 m long, 0.8 m wide, and 0.16 m between plants, with 25 plants per row. Data were collected on plant and ear characteristics. Total anthocyanin content in grain (CATg) and cob (CATo) was measured in seven of the crosses. Analysis of variance and mean comparison tests were conducted for all variables using SAS statistical software. Results. Twelve ESCs were identified with grain yield equal (p < 0.05) to the white control, but with purple grain and cob. Significant variation (p < 0.05) was observed in days to anthesis (ranging from 80 to 90 days), stalk lodging (from 0 to 12.6 %), and ear scoring (from 1.5 to 2.7). Grain texture ranged from soft to very soft among the ESCs. No association was found between grain yield and levels of CATg and CATo. Conclusion. The results from the ESCs indicate positive progress in the integration of the purple maize heterotic pattern B-49N x B-41N. However, future efforts should focus on increasing anthocyanin content in grain and cob, as well as improving grain hardness.